Recycling of blast furnace sludge by briquetting with starch binder: Waste gas from thermal treatment utilizable as a fuel. (February 2016) - Drobíková, Klára; Plachá, Daniela; Motyka, Oldřich; Gabor, Roman; Kutláková, Kateřina Mamulová; Vallová, Silvie; Seidlerová, Jana
Graphical abstract: Highlights: First-time use of starch as a binder for briquetting of blast furnace sludge. Resulting briquettes have suitable mechanical properties. Thermal treatment: 900, 1000, 1100 °C, retention period: 40 min. Resulting solid matter rich in metallic iron. First-time characterization of the waste gas – possible use as a fuel. Abstract: Steel plants generate significant amounts of wastes such as sludge, slag, and dust. Blast furnace sludge is a fine-grained waste characterized as hazardous and affecting the environment negatively. Briquetting is one of the possible ways of recycling of this waste while the formed briquettes serve as a feed material to the blast furnace. Several binders, both organic and inorganic, had been assessed, however, only the solid product had been analysed. The aim of this study was to assess the possibilities of briquetting using commonly available laundry starch as a binder while evaluating the possible utilization of the waste gas originating from the thermal treatment of the briquettes. Briquettes (100 g) were formed with the admixture of starch (UNIPRET) and their mechanical properties were analysed. Consequently, they were subjected to thermal treatment of 900, 1000 and 1100 °C with retention period of 40 min during which was the waste gas collected and its content analysed using gas chromatography. Dependency of the concentration of the compounds forming the waste gas on the temperature used was determined using Principal component analysis (PCA) and correlation matrix. Starch was found to be a very good binder and reduction agent, it was confirmed that metallic iron was formed during the thermal treatment. Approximately 20 l of waste gas was obtained from the treatment of one briquette; main compounds were methane and hydrogen rendering the waste gas utilizable as a fuel while the greatest yield was during the lowest temperatures. Preparation of blast furnace sludge briquettes using starch as a binder and their thermal treatment represents a suitable method for recycling of this type of metallurgical waste. Moreover, the composition of the resulting gas is favourable for its use as a fuel.